2022
DOI: 10.3390/jof8060585
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Infection with SARS-CoV-2 and Pneumocystis jirovecii in Immunocompromised and Immunocompetent Individuals

Abstract: Coronavirus disease 2019 (COVID-19) may occur with concurrent infections caused by bacterial and fungal microorganisms. This systematic review evaluated studies reporting concomitant COVID-19 and Pneumocystis jirovecii pneumonia (PJP). We found 39 patients (74% male, median age: 56.8 (range: 11–83) years), including 66% immunosuppressed individuals (23% HIV-infected and 41% on long-term corticosteroid therapy). Patients were characteristically severely ill (mechanical ventilation: 70%), associated with 41% mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Among the opportunistic coinfections reported in COVID-19 patients, P. jirovecii is one of the most concerning, as it shares similar clinical features with COVID-19 (e.g., bilateral multifocal infiltrates and profound hypoxemia) and may worsen the prognosis and increase the mortality. [ 22 24 ] Alanio et al [ 25 ] reported a high prevalence (9%) of SARS-Cov2 and P.Jirovecii co-occurrence in the ICU setting.However, the incidence and prevalence of PCP in COVID-19 patients are still unknown and may vary depending on the geographic region, the population characteristics, and the diagnostic methods used.…”
Section: Discussionmentioning
confidence: 99%
“…Among the opportunistic coinfections reported in COVID-19 patients, P. jirovecii is one of the most concerning, as it shares similar clinical features with COVID-19 (e.g., bilateral multifocal infiltrates and profound hypoxemia) and may worsen the prognosis and increase the mortality. [ 22 24 ] Alanio et al [ 25 ] reported a high prevalence (9%) of SARS-Cov2 and P.Jirovecii co-occurrence in the ICU setting.However, the incidence and prevalence of PCP in COVID-19 patients are still unknown and may vary depending on the geographic region, the population characteristics, and the diagnostic methods used.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), can weaken the host’s immune system and increase the risk of secondary infections with bacterial and fungal pathogens, including P. jirovecii [ 223 , 224 , 225 ]. There have been approximately 100 reports of coinfection of P. jirovecii in COVID-19 patients, with some of them reviewed recently by Gioia et al [ 226 ] and Khodadadi et al [ 227 ]. The largest number of coinfection cases (in non-HIV/AIDS) was reported from France (34 cases), followed by Italy (22 cases) and Pakistan (10 cases) ( Figure 3 and Table S3 [ 15 , 224 , 225 , 226 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 ,…”
Section: Immunodeficient Conditions and Risk Factors For Pcpmentioning
confidence: 99%
“…While it is clear that the incidence of PCP is much lower in COVID-19 than that in AIDS, the incidence of PCP in COVID-19 seems to be underestimated for various reasons [ 223 , 226 , 286 ], including the difficulties in distinguishing between these two diseases due to their similarities in clinical symptoms and manifestations, the lack of awareness or attention to PCP, and the lack of access to sensitive diagnostic tests for PCP, particularly during the challenging pandemic era. A study using a highly sensitive qPCR assay identified a prevalence of 9% of P. jirovecii infection in critically ill COVID-19 patients [ 228 ], supporting the possibility of a high prevalence of PCP in COVID-19 patients and highlighting the importance of using a sensitive, pathogen-specific diagnostic method.…”
Section: Immunodeficient Conditions and Risk Factors For Pcpmentioning
confidence: 99%
“…As far as antifungal therapy is concerned, the approach should be like that for patients without COVID-19. Trimethoprim/sulfamethoxazole remains the preferred initial therapy for most patients [105].…”
Section: Pneumocystis Jiroveciimentioning
confidence: 99%